Uncertainty and change: Survey evidence of firms' subjective beliefs - Ruediger Bachmann; Kai Carstensen; Stefan Lautenbacher; Martin Schneider (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
This paper studies how managers plan under uncertainty. In a new panel survey of German manufacturing firms, we observe both forecasts of sales growth and a quantitative measure of subjective uncertainty. We show that subjective uncertainty reflects change experienced by firms: it is high when growth is either unusually low or unusually high. Subjective uncertainty is more than conditional volatility: while more volatile firms are typically more uncertain, experienced change alone increases uncertainty, consistent with a model of learning. Uncertainty over our sample is mostly idiosyncratic but varies substantially over time and leads managers to plan lower employment and prices.
Keywords: C83; D22; E20; E23; 330; expectation formation; firms; measurement; subjective uncertainty; survey data